Incidence of Listeria in fish and shellfish - M.M., Prasad; Thampuran, Nirmala (Fishery Technology, 2025)
Listeria monoajlogenes has been recognized as an important food-borne pathogen since 1981 and seafoods have been implicated in several sporadic cases of Listeriosis. In the present study fresh (57), iced (49) and frozen (84) fish and shellfish from cultured ponds and commercial outlets were screened for Listeriae. Among the samples of fresh cultured fish, 1.8% contained Listeria innocua. The iced Penaeus indicus (PUD) and Penaeus monodon contained 20% Listeria spp., comprising L. innocua and L. ivanovii. Listeria spp. were detected in 14.28% of the frozen fish samples also. Listeria monocytogenes could not be detected in any of the samples.